Military Threats In The Global Sea: Implications For Indonesia’s Maritime Security Toward Golden Indonesia 2045 - Hilmansyah, Ceppi; Prakoso, Lukman Yudho (CV. Publikasi Indonesia, 2025)
Military threats in global waters are increasingly complex and significantly impact Indonesia's maritime security. Regional geopolitical dynamics, major power rivalries, and foreign military activities in strategic waters demand resilient maritime defense readiness toward the Golden Indonesia 2045 vision. This study analyzes the implications of global military threats on Indonesia's maritime security and formulates defense strategies aligned with the Golden Indonesia 2045 vision. The research uses a qualitative approach with descriptive analysis methods. Data were collected through literature studies of primary and secondary sources, including policy documents, international reports, and recent academic publications. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that global military threats significantly impact Indonesia's maritime security, particularly through foreign military presence in the South China Sea, uncoordinated military exercises, and hybrid technology developments. These threats require modernization of maritime defense systems, enhanced human resource capacity, and strengthened maritime diplomacy. Strong maritime security is a fundamental pillar in realizing the Golden Indonesia 2045 vision. Indonesia's maritime defense strategy needs to comprehensively integrate military, diplomatic, legal, and economic aspects. Modernization of primary weapons systems, human resource development, and regional cooperation are key to addressing global military threats and supporting Indonesia's achievement as a sovereign developed nation